1987
DOI: 10.1111/j.1468-2958.1987.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Content Themes in Marital Conversations

Abstract: Conversational themes can be viewed as a form of metacommunication about relationships. We suggest that the prominent themes in the conversations of spouses identify factors assumed to h a w an important effect on the relationship. Further, different ways of looking a t marriage are reflected in the use ofparticular content themes. A typology of content themes was deriwd from transcripts of conversations and the typology was used to code the discussions of married couples. The content themes of different marit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Specifically, content coding has shown that satisfied couples emphasize communal themes both in couples’ conversations (Sillars, Weisberg, Burggraf, & Wilson, 1987; Sillars, Burggraf, Yost, & Zietlow, 1992) and in couples’ free-response relationship descriptions (Fletcher, Fincham, Cramer, & Heron, 1987). Further, in the Buehlman and Gottman work (Buehlman et al, 1992; Carrere, Buehlman, Gottman, Coan, & Ruckstuhl, 2000), relational schemas were derived from narrative coding of videotaped oral history interviews of married couples.…”
Section: Methods Used To Study We-ness and Separatenessmentioning
confidence: 99%
“…Specifically, content coding has shown that satisfied couples emphasize communal themes both in couples’ conversations (Sillars, Weisberg, Burggraf, & Wilson, 1987; Sillars, Burggraf, Yost, & Zietlow, 1992) and in couples’ free-response relationship descriptions (Fletcher, Fincham, Cramer, & Heron, 1987). Further, in the Buehlman and Gottman work (Buehlman et al, 1992; Carrere, Buehlman, Gottman, Coan, & Ruckstuhl, 2000), relational schemas were derived from narrative coding of videotaped oral history interviews of married couples.…”
Section: Methods Used To Study We-ness and Separatenessmentioning
confidence: 99%
“…For example, Veroff, Sutherland, Chadiha, and Ortega (1993) found that a "we" orientation in the joint narratives of newlywed couples predicted later marital satisfaction and stability. Sillars and colleagues (Sillars, Weisberg, Burggraf, & Wilson, 1987;Sillars, Burggraf, Yost, & Zietlow, 1992) observed more communal themes (i.e., statements about shared relationship characteristics) in the conversations of satisfied couples and more individual themes (i.e., statements about separate identities or roles) in the conversations of dissatisfied couples.…”
mentioning
confidence: 93%
“…For example, Sillars, Pike, Jones, and Redmon (1983) found that marital satisfaction was higher when communication behaviors were consistent with couples' self-expressed marital ideologies. Similarly, other researchers found that the types of conversational content themes associated with marital satisfaction were contingent on couple type (Sillars, Weisberg, Burggraf, & Wilson, 1987).…”
Section: Interpretations Of Television Contentmentioning
confidence: 97%